1994
DOI: 10.1136/bjo.78.10.745
|View full text |Cite
|
Sign up to set email alerts
|

Combined trabeculotomy-trabeculectomy compared with primary trabeculectomy for congenital glaucoma.

Abstract: This paper aimed to assess the outcome of primary trabeculectomy for congenital glaucoma and to compare it with a combined trabeculotomy-trabeculectomy procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
94
1
8

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 20 publications
7
94
1
8
Order By: Relevance
“…50 On the other hand, the disadvantage of trabeculotomy is that the Schlemm's canal may not be found in 11-15% of the procedures. 19,28 In view of these limitations, some surgeons have resorted to primary trabeculectomy in the management of PDG because primary trabeculectomy is easier than goniotomy or trabeculotomy. [51][52][53][54][55] Unfortunately, many of the patients with PDG require multiple surgeries to achieve a successful outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 On the other hand, the disadvantage of trabeculotomy is that the Schlemm's canal may not be found in 11-15% of the procedures. 19,28 In view of these limitations, some surgeons have resorted to primary trabeculectomy in the management of PDG because primary trabeculectomy is easier than goniotomy or trabeculotomy. [51][52][53][54][55] Unfortunately, many of the patients with PDG require multiple surgeries to achieve a successful outcome.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,8,[24][25][26] In the search for the best surgical treatment of developmental glaucoma, combined trabeculotomy-trabeculectomy (CTT) owing to its obvious advantages over conventional procedures has emerged as the new treatment modality. [27][28][29] Over the last decade, the good success rate of CTT reported by Elder 28 has been substantiated by other institutions and paediatric ophthalmologists. [30][31][32][33][34][35][36] The functional outcome of patients with PDG is poor; no more than 40-50% of these children achieve a vision of 20/50 or better.…”
mentioning
confidence: 92%
“…Our success rate with initial surgery is significantly better than most of the reported results of initial goniotomy [6][7][8] or trabeculotomy ab externo. [9][10][11][28][29][30][31][32][33] The superior results of the combined procedure may be because of the dual outflow pathway as explained by Elder, 35 and Mandal and co-workers 3,12,[14][15][16][17][18] The additional advantage of CTT is that it allows greater surgical flexibility in advanced buphthalmos. For example, conversion to trabeculectomy is feasible in cases where identification of Schlemm's canal is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Although the combined procedure seems to have a favourable outcome, the advantages of this procedure over trabeculotomy or trabeculectomy were not statistically significant after 2 years. Elder 35 compared primary trabeculectomy with CTT and found the latter to be superior. In the present study, all patients underwent CTT and our results are comparable to those reported by Elder 35 and better than the results of goniotomy [6][7][8] or trabeculotomy, 9,11,[28][29][30][31][32][33] or trabeculectomy alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation